The Role of Oxidative Stress in Autism Spectrum Disorder Pathophysiology, Diagnosis and Treatment - Aleksandra Kuźniar-Pałka (Biomedicines)
Autism spectrum disorder (ASD) is a significant health problem with no known single cause. There is a vast number of evidence to suggest that oxidative stress plays an important role in this disorder. The author of this article reviewed the current literature in order to summarise the knowledge on the subject. In this paper, the role of oxidative stress is investigated in the context of its influence on pathogenesis, the use of oxidative stress biomarkers as diagnostic tools and the use of antioxidants in ASD treatment. Given the heterogeneity of ASD aetiology and inadequate treatment approaches, the search for common metabolic traits is essential to find more efficient diagnostic tools and treatment methods. There are increasing data to suggest that oxidative stress is involved in the pathogenesis of ASD, both directly and through its interplay with inflammation and mitochondrial dysfunction. Oxidative stress biomarkers appear to have good potential to be used as diagnostic tools to aid early diagnosis of ASD. The results are most promising for glutathione and its derivatives and also for isoprostanses. Probably, complex dedicated multi-parametric metabolic panels may be used in the future. Antioxidants show good potential in ASD-supportive treatment. In all described fields, the data support the importance of oxidative stress but also a need for further research, especially in the context of sample size and, preferably, with a multicentre approach.